Development of a Correspondence Information System at Santa Maria Homba Karipit Catholic High School - Martha Ina Buku; Ardiyanto Dapadeda; Diana Reby Sabawali (Journal Innovations Computer Science, 2026)
While digital transformation has become a baseline expectation in modern school administration, correspondence archive management at Santa Maria Homba Karipit Catholic Senior High School remains entirely manual — producing measurable inefficiencies in document storage and persistent delays in data retrieval. Staff rely on physical logbooks and disconnected tools, with no centralized system to track letter histories or generate timely reports. This study designed and developed a web-based Correspondence Management Information System to digitize the school's administrative procedures. The methodology employed systematic requirements analysis, realized through Context Diagrams and Data Flow Diagrams (DFD) up to Level 2, alongside the design of a relational database. The resulting system integrates three user roles — Admin, Head of Administration, and School Principal — into a unified platform for managing incoming and outgoing letters and generating periodic reports. System testing across 24 test cases returned a 100% pass rate. Deployment reduced per-document processing time from fifteen minutes to two minutes, minimized the risk of physical archive loss, and provided school leadership with faster, more reliable access to correspondence records to support administrative decision-making.